About possibility of operative management by cement concrete properties - Тевяшев, А.Д.; Шитиков, Е.С. (Eastern-European Journal of Enterprise Technologies, 2010)
Results of experimental researches on operative management by cement concrete properties are resulted by their manufacture on the basis of three methods: estimations of activity of cements; ultradispersible nanomodifier; ultrasonic handling of water before its mixing with cement.